Cultural Contributors to Negative Emotionality: A Multilevel Analysis from the Joint Effort Toddler Temperament Consortium - Lecannelier-Acevedo, F (SAGE Publications Ltd, 2021)
This study advances the cross-cultural temperament literature by comparing temperament ratings of toddlers from 14 nations. Multilevel modeling (MLM) procedures were utilized to regress negative emotionality (NE) and component subscales on Hofstede’s cultural value dimensions while controlling for age and gender. More individualistic values were associated with lower NE, and component discomfort, fear, motor activity, perceptual sensitivity, and soothability scales. The discomfort subscale was negatively associated with power distance and positively associated with masculine cultural values. Higher ratings of shyness were related to a more long-term cultural orientation. Results illustrate the feasibility of an MLM approach to cross-cultural research and provide a new perspective on the intersection of culture and temperament development. Limitations and future implications are discussed. © The Author(s) 2021.